2008
DOI: 10.1097/ccm.0b013e31818b9153
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide as a marker for sepsis-induced myocardial depression in intensive care patients*

Abstract: These results indicate that plasma BNP concentration represents a reliable marker for identification of patients developing sepsis-induced myocardial depression. In addition, BNP concentration on day 5 may be used as a prognostic marker to identify patients with an elevated risk for an adverse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 30 publications
3
78
0
3
Order By: Relevance
“…N-terminal prohormone of brain natriuretic peptide has been found to be a useful marker in the diagnosis, management, and prognosis of patients with congestive heart failure. In early stages of septic shock, impaired myocardial function plays an important prognostic role [43]. There is a close inverse relationship between increased plasma NT-proBNP concentrations and depressed left ventricular ejection fraction, and plasma NT-proBNP concentration represents a reliable marker for identification of patients developing sepsis-induced myocardial depression [43].…”
Section: Discussionmentioning
confidence: 99%
“…N-terminal prohormone of brain natriuretic peptide has been found to be a useful marker in the diagnosis, management, and prognosis of patients with congestive heart failure. In early stages of septic shock, impaired myocardial function plays an important prognostic role [43]. There is a close inverse relationship between increased plasma NT-proBNP concentrations and depressed left ventricular ejection fraction, and plasma NT-proBNP concentration represents a reliable marker for identification of patients developing sepsis-induced myocardial depression [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognostic values of biomarkers in sepsis remain controversial, cTnT [37], BNP [38], and hsCRP [39] have been reported to be prognostic predictors in septic patients. Therefore, we investigated the prognostic value of these biomarkers in our patients and assessed the potential relationships of these biomarkers with GLS.…”
Section: Discussionmentioning
confidence: 99%
“…Brain natri- uretic peptides along with other cardiac markers such as troponin have been found significantly elevated in sepsis and septic shock. 6,7 Few studies coming out in the last few years showed a good prognostic power of BNP to predict severity and prognosis of pneumonia. [8][9][10][11][12] Patients with pneumonia frequently face hypoxemia or respiratory failure which can be just part of the more complex SIRS and which can affect heart function.…”
Section: Discussionmentioning
confidence: 99%